If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-7)+2x=6-3(2x+9)
We move all terms to the left:
4(x-7)+2x-(6-3(2x+9))=0
We add all the numbers together, and all the variables
2x+4(x-7)-(6-3(2x+9))=0
We multiply parentheses
2x+4x-(6-3(2x+9))-28=0
We calculate terms in parentheses: -(6-3(2x+9)), so:We add all the numbers together, and all the variables
6-3(2x+9)
determiningTheFunctionDomain -3(2x+9)+6
We multiply parentheses
-6x-27+6
We add all the numbers together, and all the variables
-6x-21
Back to the equation:
-(-6x-21)
6x-(-6x-21)-28=0
We get rid of parentheses
6x+6x+21-28=0
We add all the numbers together, and all the variables
12x-7=0
We move all terms containing x to the left, all other terms to the right
12x=7
x=7/12
x=7/12
| y+6/2=14 | | (x-1)^2=25 | | d=1/2.20(20-3) | | 10•x=4 | | 14=5/m | | 7k+16=k+40 | | 5r^2-36=10r | | x/3=x/7+10/3 | | 15x^2-5x-30=0 | | -8(12+6r)-9(1+3r)=45 | | w=17+1 | | X/9+y/6=1/3 | | 2a^2+15a-27=0 | | 3x=12=24 | | 2(x+3)=4x+10+2 | | 3x/2+9/14=22/7 | | 5.5x+5=120.5 | | -5(12-9n)-9(1-6n)=30 | | x/5-3=9/10 | | 4x/3-x/9=11/27 | | z/5-7=11/8 | | 5x^2+7=13 | | 2.6x-5.68=8.1 | | 30x+3=x+2/9 | | 3(x+1=21 | | 5.5x=25=50.5 | | 11(-7v+6)+8(12v+4)=3 | | 7.5m+3m-m=28.5 | | (((17+y)/y)+((32+y)/y))=100 | | 3(6x-3)=12x | | 1-5n-8(1+7n)=-8+1+n | | -29+2m=-3(8m+1) |